How hot is too hot for people? A review of empirical models of perceptual, physiological and functional limits of human heat tolerance - Filingeri, D.; Koch Esteves, N. (Experimental Physiology, 2026)
How hot is too hot for people? This is a question that human thermal physiologists are asked often by a variety of knowledge users across the public and private sectors, who have grown aware of the negative impact of global warming on people's health and quality of life. The aim of this paper is to provide a narrative review of models that quantify the limits of human heat tolerance across perceptual, physiological and functional domains. Several models exist that have identified critical environmental limits for heat tolerance across the perceptual, physiological and functional domains. However, no model is currently available that has evaluated all domains of heat tolerance concurrently and in the same participant cohort. Hence, by combining evidence from these models, here we propose a new holistic framework of heat tolerance that can help more comprehensively characterise the full spectrum of possible human responses to heat stress under free-living conditions. This framework highlights that human heat tolerance varies largely across the perceptual, physiological and functional domains, and that it is conceptually organised in line with the human body's ability to regulate body temperature via behavioural and autonomic responses. While our new framework presents limitations in its generalisability beyond healthy young adult cohorts, we hope that it will inspire the design of new holistic research on human heat tolerance in a broader range of participant cohorts, to better inform person-centred heat resilience policies and interventions that protect human health and life quality under a warming climate.